Monte Carlo simulation of gold nanoparticles for X-ray enhancement application - Dheyab, Mohammed Ali; Aziz, Azlan Abdul; Rahman, Azhar Abdul; Ashour, Nabeel Ibrahim; Musa, Ahmed Sadeq; Braim, Farhank Saber; Jameel, Mahmood S. (Biochimica et biophysica acta. General subjects, 2023)
Gold nanoparticles (Au NPs) are regarded as potential agents that enhance the radiosensitivity of tumor cells for theranostic applications. To elucidate the biological mechanisms of radiation dose enhancement effects of Au NPs as well as DNA damage attributable to the inclusion of Au NPs, Monte Carlo (MC) simulations have been deployed in a number of studies. This review paper concisely collates and reviews the information reported in the simulation research in terms of MC simulation of radiosensitization and dose enhancement effects caused by the inclusion of Au NPs in tumor cells, simulation mechanisms, benefits and limitations. In this review, we first explore the recent advances in MC simulation on Au NPs radiosensitization. The MC methods, physical dose enhancement and enhanced chemical and biological effects is discussed, followed by some results regarding the prediction of dose enhancement. We then review Multi-scale MC simulations of Au NP-induced DNA damages for X-ray irradiation. Moreover, we explain and look at Multi-scale MC simulations of Au NP-induced DNA damages for X-ray irradiation. Using advanced chemical module-implemented MC simulations, there is a need to assess the radiation-induced chemical radicals that contribute to the dose-enhancing and biological effects of multiple Au NPs. •Comprehensive overview of recent advancements in MC simulation on Au NPs.•Exploring the recent advances in MC simulation on Au NPs radiosensitization.•Limitations of MC simulation of Au NPs for theranostic application are discussed.